FOREIGN EXPERIENCE ON PREPARATION OF FUTURE TEACHERS FOR THE ACTIVITY OF MUSEUM PEDAGOGY (Scientific journal of the Fergana State University, 2024)
In this article, the interaction of the museum with educational institutions, as well as the experiences of the USA, Germany and Russia on the preparation of future teachers in pedagogical universities for the activity of museum pedagogy were highlighted and opinions were given on future teachers preparing at pedagogical universities about the knowledge, skills and qualifications that should be acquired for the activity of "museum pedagogy".